PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN SENI TARI PAKARENA DI SMP KEMALA BHAYANGKARI MAKASSAR - Musnida Hukmiddin; Syahkruni Syahkruni; Andi Ihsan; Nurhikmah Nurhikmah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to design, test the validity and practicality, and measure the effectiveness of the Jigsaw type cooperative learning model based on NIDA syntax (Navigate, Introduction, Discuss, Action) in improving students' understanding and skills in learning the art of Padengan dance. The products developed in this research include learning model books, teacher guides, as well as learning tools in the form of lesson plans and research instruments. This research uses research and development (R&D) methods with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects consisted of teachers and students of class VIII SMP Kemala Bhayangkari Makassar. Data collection techniques include interviews, observation, documentation, questionnaires, as well as testing product validity and practicality through expert assessments and user responses. The results of the research show that: (1) there is a need for a learning model that is more interactive and oriented towards local culture in learning dance, (2) the Jigsaw type cooperative learning model that was developed has been validated by experts and was declared feasible and practical to implement, (3) the implementation of this model received a positive response from teachers and students, increasing student involvement in learning, and (4) this learning model was proven to be effective in increasing students' conceptual understanding, motor skills and cultural appreciation of Padengan Dance. With these findings, it is hoped that the Jigsaw type cooperative learning model based on NIDA syntax can become a reference for arts and culture teachers in increasing the effectiveness of dance learning in junior high schools. Keyword: Jigsaw, Model Pembelajaran Kooperatif, Pembelajaran Seni Tari, Saintaks NIDA, Tari Pakarena. Abstrak: Penelitian ini bertujuan untuk mendesain, menguji validitas dan kepraktisan, serta mengukur efektivitas model pembelajaran kooperatif tipe Jigsaw berbasis sintaks NIDA (Navigate, Introduction, Discuss, Action) dalam meningkatkan pemahaman dan keterampilan siswa dalam pembelajaran seni tari Pakarena. Produk yang dikembangkan dalam penelitian ini meliputi buku model pembelajaran, panduan guru, serta perangkat pembelajaran berupa RPP dan instrumen penelitian.Penelitian ini menggunakan metode penelitian dan pengembangan (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian terdiri dari guru dan siswa kelas VIII SMP Kemala Bhayangkari Makassar. Teknik pengumpulan data mencakup wawancara, observasi, dokumentasi, kuesioner, serta uji validitas dan kepraktisan produk melalui penilaian ahli dan respons pengguna. Hasil penelitian menunjukkan bahwa: (1) terdapat kebutuhan terhadap model pembelajaran yang lebih interaktif dan berorientasi pada budaya lokal dalam pembelajaran seni tari, (2) model pembelajaran kooperatif tipe Jigsaw yang dikembangkan telah divalidasi oleh para ahli dan dinyatakan layak serta praktis untuk diterapkan, (3) implementasi model ini mendapat respons positif dari guru dan siswa, meningkatkan keterlibatan siswa dalam pembelajaran, serta (4) model pembelajaran ini terbukti efektif dalam meningkatkan pemahaman konsep, keterampilan motorik, dan apresiasi budaya siswa terhadap Tari Pakarena. Dengan temuan ini, diharapkan model pembelajaran kooperatif tipe Jigsaw berbasis sintaks NIDA dapat menjadi referensi bagi guru seni budaya dalam meningkatkan efektivitas pembelajaran seni tari di sekolah menengah pertama. Kata kunci: Jigsaw, Cooperative Learning Model, Dance Learning, NIDA Saintaks, Padengan Dance.